Biological treatment of biowaste as an innovative source of CO—The role of composting process - Sobieraj, Karolina; Stegenta-Dąbrowska, Sylwia; Luo, Gang; Koziel, Jacek A.; Białowiec, Andrzej (Frontiers in Bioengineering and Biotechnology, 2023)
Carbon monoxide (CO) is an essential “building block” for producing everyday chemicals on industrial scale. Carbon monoxide can also be generated though a lesser-known and sometimes forgotten biorenewable pathways that could be explored to advance biobased production from large and more sustainable sources such as bio-waste treatment. Organic matter decomposition can generate carbon monoxide both under aerobic and anaerobic conditions. While anaerobic carbon monoxide generation is relatively well understood, the aerobic is not. Yet many industrial-scale bioprocesses involve both conditions. This review summarizes the necessary basic biochemistry knowledge needed for realization of initial steps towards biobased carbon monoxide production. We analyzed for the first time, the complex information about carbon monoxide production during aerobic, anaerobic bio-waste treatment and storage, carbon monoxide-metabolizing microorganisms, pathways, and enzymes with bibliometric analysis of trends. The future directions recognizing limitations of combined composting and carbon monoxide production have been discussed in greater detail.